2022
DOI: 10.1101/2022.03.30.486445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Importin α/β Promote Kif18B Microtubule Association to Spatially Control Microtubule Destabilization

Abstract: Tight regulation of microtubule dynamics and microtubule organization is necessary for proper spindle assembly and chromosome segregation. The microtubule destabilizing Kinesin-8, Kif18B, controls astral microtubule dynamics and spindle positioning. Kif18B interacts with importin alpha/beta as well as with the plus-tip tracking protein EB1, but how these associations modulate Kif18B activity or function is not known. We mapped the key binding sites on Kif18B, made residue-specific mutations, and assessed their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Additionally, a recent study by Shrestha et al . found that importin α/β binding to the microtubule destabilizing Kinesin-8, Kif18B, directly regulates its ability to control microtubule dynamics and spindle positioning by altering its binding to the microtubule lattice (Shrestha et al, 2022). An importin complex association may even regulate MAP function upon nuclear envelope breakdown (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study by Shrestha et al . found that importin α/β binding to the microtubule destabilizing Kinesin-8, Kif18B, directly regulates its ability to control microtubule dynamics and spindle positioning by altering its binding to the microtubule lattice (Shrestha et al, 2022). An importin complex association may even regulate MAP function upon nuclear envelope breakdown (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, importin binding controls the efficiency of microtubule nucleation by TPX2 via selectively blocking the interaction with microtubule nucleation intermediates (Roostalu et al, 2015). Additionally, a recent study by Shrestha et al found that importin α/β binding to the microtubule destabilizing Kinesin-8, Kif18B, directly regulates its ability to control microtubule dynamics and spindle positioning by altering its binding to the microtubule lattice (Shrestha et al, 2022). An importin complex association may even regulate MAP function upon nuclear envelope breakdown (i.e.…”
Section: Conserved Patch Within Basic Linker May Have Additional Func...mentioning
confidence: 99%